Wisconsin Indian Head Country-A Guide to the Past: Real and Mythical - Geniusz, Errol (My University, 2013)
In the 1930s, businessmen in the Eau Claire area and resort owners in Northwestern Wisconsin, an area decimated by logging, collaborated as a group with the hope of promoting tourism to the area and boost the local economy. This group of men and resort owners created the organization Wisconsin Indian Head Country Inc. and to incorporate the area as "authentic" they created and used an Indian head image. Eighty years later many organizations and businesses around Wisconsin continue to use them on maps and brochures to draw tourists to the area. This image is used over much of the Northwest part of Wisconsin. The Indian head image outlines the northwest part of the state of Wisconsin on many tourist maps. The face of the Indian head is created by the St. Croix River, the forehead is made up of the Minnesota and Wisconsin border and the headdress is the Apostle Islands. The purpose behind this research is to learn about the history, origins, purpose, and use of this iconic image and to discuss the local history of this region, including that of Native people and their role in promoting tourism. Recently, there has been much controversy over the use of Indian images as mascots for schools and professional teams around the country. One image that has been over looked and is ever so prevalent is the Wisconsin Indian head image. This research seeks to answer the following questions: What is the purpose of using this logo? Have Indians been a part of the tourism industry and if so what was their role? Is there some hope in the future for change?
Keywords: Wisconsin Indian Head Country Inc; Tourism -- Wisconsin -- History; Logos (Symbols) -- Wisconsin -- History; Indians as mascots -- Wisconsin; Stereotypes (Social psychology) -- Wisconsin; Minorities in advertising -- Wisconsin